BAHAYA KETIDAKPATUHAN MENGGUNAKAN APD DI RUMAH SAKIT - Fitriyani, Aris; Sukrillah, Ulfah Agus; Walin, Walin (JURNAL KEPERAWATAN MERSI, 2013)
Background. Various studies have shown the prevalence of problem occurring among employees of officers of healtfacilities is quite high. Workplace hazards both physical, biological, or chemical needs to be controlled in such a way so as to create a healty working environment, safe and safety. Various control measures can be taken to deal with workplace hazard, but technically control the hazard it self and is considered the most effective, while the use of personal protective equipment is the last option.Method. The study design is a map analysis research. Respondents used is from the results of several studies related to the used of APD in some hospitals.This sample taken from the nurse-patient department in the room both indoors are at risk for such diseases transmitted diseases in the wards and in the intensive care ward such as ICU. Research tool used is the result of research from various studies conducted by analyzing.Result. Result of research in the Banyumas hospital showed that the level of compliance in the use of APD pers that already exist in the form of ward Bougenville and Cempaka action suit, mask and gloves.100% of the interview informants acquainted with APD, traditions, beliefs and value systems adopted in compliance with APD use shows 90% of informants gave a positive response, while 10% of informants have a bad habit of regular informants must commence. The results Chrysmadani (2011) showed that most of the 14 people (58%) felt the availability of equipment in the hospital Graha Husada Gresik and none of the nurses who feel the availability of a tool is still lacking. Medium Spearman rank test statistic, obtained significance value p = 0.002 which is smaller than 0.05, so there is a connection with the limited means adherence nurses in hospitals Graha Husada GresikConclusion. Based on the analysis of the research map can be concluded that the hospital has had an opportunity to cultivate safety 2.9 times more adherent to run universal precautions including APD usage behavior on nurse. Nurses who are obedient to the use of APD to be healthy and fit in the general workup check up, so avoid nosocomial infections. Instead caregivers who do not adhere to the use of APD will result in opportunities for nosocomial infections such as tuberculosis minimal contact with the suspect and SGOT and SGPT increased revenue to the risk of developing hepatitis in less compliant caregivers on the use of APD.